Perinatal Mortality And Pregnancy Wastage In Ten Punjab Villages During 1991-1996 - A Population Based Study - Sachar R.K; Soni R.K; Singh W.P; Dhot Ramnik; Gill P.J.S; Arora Sona; Singh Hari; Dhiman B (Wolters Kluwer Medknow Publications, 1998)
Research question: What is the extent of perinatal mortality and pregnancy wastage in rural Punjab and what are risk factors for the same. Objective: To quantify the perinatal; wastage and risk factors including the prevalence of these factors to determine the loss attributable to these factors in ten Punjab villages during the period 1991-1996. Study Design: Case control. Sample Size: 2519 pregnant women with Known outcome of pregnancy. Study Variables: Cause, timing and factors affecting perinatal mortality and pregnancy wastage (viz Wt.<40kg; Ht, <152cm,BMI, <20 illiteracy, birth to conception interval <100wks, Prematurity (Gestation <37 wks). Registered in IIIrd trimester, Registered in IInd Trimester, Home delivery). Outcome variables: Contribution of these factors in perinatal loss and pregnancy wastage. Analysis; Percentages, Odds ratio, confidence interval and population attributable risk%. Results: The perinatal mortality rate was 34.57/1000 and pregnancy wastage was 7.23%. Prematurity was the leading cause of perinatal loss. 31.25% of perinatal deaths took place within 24 hours and 87.5% within 96 hours. In case of perinatal mortality the odds ration were significant (p<0.05) for the following risk factors: weight, height, body mass index, illiteracy, birth to conception interval <1000 weeks, prematurity, registration of pregnancy in IInd trimester, registration of pregnancy in IIIrd trimester, home delivery. In case of pregnancy wastage the odds ratio were significant for the following risk factors: weight, height, body mass index, illiteracy, birth to conception interval <100weeks, prematurity, past history of abortion and low socio-economic status.